Endocytotic potential governs magnetic particle loading in dividing neural cells: studying modes of particle inheritance. (February 2016) - Tickle, Jacqueline A; Jenkins, Stuart I; Polyak, Boris; Pickard, Mark R; Chari, Divya M
Aim: To achieve high and sustained magnetic particle loading in a proliferative and endocytotically active neural transplant population (astrocytes) through tailored magnetite content in polymeric iron oxide particles.Materials & methods: MPs of varying magnetite content were applied to primary-derived rat cortical astrocytes ± static/oscillating magnetic fields to assess labeling efficiency and safety.Results: Higher magnetite content particles display high but safe accumulation in astrocytes, with longer-term label retention versus lower/no magnetite content particles. Magnetic fields enhanced loading extent. Dynamic live cell imaging of dividing labeled astrocytes demonstrated that particle distribution into daughter cells is predominantly 'asymmetric'.Conclusion: These findings could inform protocols to achieve efficient MP loading into neural transplant cells, with significant implications for post-transplantation tracking/localization.